ANALISIS DAMPAK SOSIAL EKONOMI PASCA BENCANA DI KABUPATEN PAMEKASAN (Studi Kasus Banjir, Longsor dan Kekeringan di Pamekasan 2007) - Qaiyim Asy'ari (J-MACC, 2018)
The climate in Pamekasan district is classified as AW climate, namely tropical climate, wet and dry clear rainfall of at least one month <60 mm (2.4 ich). While according to the classification based on wet months and dry months to help agricultural businesses, especially rice, Pamekasan regency is classified as climate D, which means that it is generally classified as a dry area so that along the kamarau potential drought in Pamekasan regency is very vulnerable and spread in 11 sub-districts of 13 districts in the district pamekasan. The purpose of the research activities on post-disaster socio-economic impacts in Pamekasan district is to obtain data and information about disaster-prone areas as well as socio-economic impacts on the community